HUBUNGAN PENGETAHUAN REMAJA PUTRI TENTANG PERSONAL HYGIENE SAAT MENSTRUASI DI WILAYAH KERJA PMB SURATMI - Dyka Aidina; Sarmauli Franshisca Sihombing; Tri Ribut Sulistiyawati (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
In general, young women still have beliefs and habits that tend to be wrong when viewed from the aspect of personal hygiene during menstruation. This is evidenced by the fact that there are still many young women who do not understand about menstruation and its relationship to reproductive health. This study uses a quantitative descriptive study design. This research was conducted at PMB Suratmi Batam City, Riau Islands. The population used in this study were young women, amounting to 298 people. The sample in this study is the total population of 298 people with the sampling technique using total sampling. The data measurement method uses a questionnaire that is distributed online using the help of google forms, while the data analysis method uses the help of statistical applications. The source of data in this study is primary data where the data is fully obtained by researchers from research results. Based on the results of a study involving 298 young women, it can be concluded that the respondent's level of knowledge is in the good category, then in responding to the first menstruation the respondent says he tells about his menstruation to the mother, and based on the action, the respondent's personal hygiene during menstruation is in the good category.